Analysis of older patients hospitalized for burns in Brazil - Daronch, Oona Tomiê [UNESP]; Secanho, Murilo Sgarbi [UNESP]; Neto, BALDUINO FERREIRA DE MENEZES [UNESP]; Palhares, Aristides Augusto [UNESP]; Marcante, Renata Fernanda Ramos [UNESP] (Thieme, 2023)
Objective: Analyze the available variables on the Department of Informatics of the Unified Health System (DATASUS) platform of hospitalized burn older people and compare older people over and under 80. Method: A retrospective study collected data in DATASUS from January 2009 to December 2019. Patients aged 60-79 years or older and 80 years or older were included in the study, with variables such as time average hospitalization, healthcare costs, and mortality rate. Results: During the studied period, 168,955 patients aged 60-79 and 50,410 aged 80 or over suffered burns. The highest mortality occurs in flame accidents, followed by contact burns, third-place scalds, and electrical burns (p=0.01). The incidence of hospitalizations in people over 80 is higher than in those aged 60-79 (p<0.001). There was a directly proportional relationship between age and length of stay only in the most advanced age groups. It was also possible to verify that the higher the health costs, the higher the mortality rate. Conclusion: The length of stay is longer in older patients, and the longer average stay is related to a higher mortality rate. Furthermore, a greater number of days of hospitalization does not result in a lower mortality rate, showing that prevention and adequate management of supplies are more important than a large investment in treatment.
Análise de pacientes idosos internados por queimaduras no Brasil
Keywords: Accidents; Aged; Brazil; Burns; Epidemiology; Frail elderly